Analysis of social educators’ and parents’ cooperation possibilities: promoting and hindering factors - Alifanovienė, Daiva; Vaitkevičienė, Asta; Musvicienė, Žydra (Social Welfare: Interdisciplinary Approach, 2014)
The article deals with the peculiarities of social educators’ and parents’ cooperation possibilities in schools. The article presents the analysis of a qualitative semi-structured interview with parents (N=15) and a quantitative study with school educators (N=176). Employing targeted content analysis of parents’ and teachers’ opinion and written quantitative questionnaire, the peculiarities and possibilities of the cooperation between the participants of the educational process have manifested themselves. These include possible cooperation areas, factors promoting and hindering this process.